Alice in wonderland ebook - Carroll, Lewis (Alice in Wonderland, 2012)
Alice in Wonderland (also known as Alice's Adventures in Wonderland ), from 1865, is the peculiar and imaginative tale of a girl who falls down a rabbit-hole into a bizarre world of eccentric and unusual creatures. Lewis Carroll's prominent example of the genre of "literary nonsense" has endured in popularity with its clever way of playing with logic and a narrative structure that has influence generations of fiction writing.